2015
DOI: 10.1063/1.4921858
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity improvement of Cerenkov luminescence endoscope with terbium doped Gd2O2S nanoparticles

Abstract: Articles you may be interested inOptical emission, vibrational feature, and shear-thinning aspect of Tb3+-doped Gd2O3 nanoparticle-based novel ferrofluids irradiated by gamma photons Suppression of luminescence quenching at the nanometer scale in Gd2O3 doped with Eu3+ or Tb3+: Systematic comparison between nanometric and macroscopic samples of life-time, quantum yield, radiative and nonradiative decay rates J. Appl. Phys. 110, 094317 (2011); 10.1063/1.3658810 Vacuum ultraviolet spectroscopic properties of rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The researchers explored this empirical concept using the modified Stober method for the preparation of the bifunctional Tb complex-based NPs. 145 Moreover, Xin Cao et al also indicated improvement in the sensitivity of the Cerenkov luminescence endoscope by using Tb-doped gadolinium oxide sulfate NPs for effective use in the clinical diagnosis of gastrointestinal tract tumors, 146 summarized in Figure 6(a−d).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers explored this empirical concept using the modified Stober method for the preparation of the bifunctional Tb complex-based NPs. 145 Moreover, Xin Cao et al also indicated improvement in the sensitivity of the Cerenkov luminescence endoscope by using Tb-doped gadolinium oxide sulfate NPs for effective use in the clinical diagnosis of gastrointestinal tract tumors, 146 summarized in Figure 6(a−d).…”
Section: Diagnosismentioning
confidence: 99%
“…Following information pertains to the outcomes of the in vivo experiment: (a) an image of a hairless mouse, (b) a combined image of white light and luminescence that displays the local pseudotumor area captured via CLE, (c) a correlation between the intensity of emitted luminescence obtained through CLE and the activity of 68Ga, and (d) signal to background ratio (SBR) in relation to the activity of 68Ga, reproduced with permission from ref . Copyright 2015, AIP Publishing.…”
Section: Terbium-based Nps (Tbnps) For Biomedical Applicationsmentioning
confidence: 99%
“…Carpenter et al [ 30 ] demonstrated the down-conversion of Cerenkov light emitted from 18 F by barium yttrium fluoride nanoscrystals doped with terbium and europium. Instead, excitation by 68 Ga terbium-doped Gd nanoparticles revealed a significant improvement in detection sensitivity for clinical diagnoses of gastrointestinal tract tumors [ 31 ]. The fact that gamma radiation is the major cause of Europium Oxide (EO) NP emissions was demonstrated by Hu et al [ 32 ].…”
Section: Nanoparticles For Imaging and Therapy Using Cerenkov Sourmentioning
confidence: 99%
“…This strategy reduces the ambient noise using the inside of the living body as a dark space, and the proof of concept of endoscopic CLI results was therefore demonstrated. Through the development of novel imaging probes and imaging systems, the subsequent studies improved the performance of endoscopic CLI and the clinical translation potential was discussed . In 2015, endoscopic CLI succeeded to detect the gastrointestinal tumors in a clinical trial involved four patients .…”
Section: Introductionmentioning
confidence: 99%